Otentisitas al-Qur’an dalam Tafsir Syiah: Penolakan al-Tusi, al-Tabarsi dan al-Tabataba‘i Terhadap Tahrif al-Qur’an - Zaim, Zaimul Asroor; Cemal Sahin (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2022)
The accusation of changing the Qur’an (taḥrif al-Qur’ān) is often leveled against the Shia. In fact, the Shia are considered to have their own Qur’an that is different from the standard Mushaf ‘Uthmān ī. This then implies accusations of heresy against them. This article will examine the views of three major Shia scholars on the authenticity of the Qur’an, namely al-Ṭūsī, al-Ṭabarsī, and al-Ṭabāṭabā ‘ī. The exploration of ideas is done by looking comparatively at their works of Qur’anic exegesis. In the end, this article finds that the narrative of naskh al-tilāwah (erasure of the texts of the Qur’an) that is widely attached to Shia is a history that contradicts the Qur’an. Although all three have different descriptions, they have the same idea, which is to reject the existence of changes (taḥrīf) in the Qur’an. Thus, the existing Qur’an, the standard Qur’an of the Mushaf ‘Uthmānī, is the authentic Qur’anic text.